(untitled) (Archive of Conferences, 2021)
Today, the leader of our state is committed to the development of Uzbekistanin accordance with the Action Strategy put forward in five sustainable areas;to implement absolutely new ideas and trends for sustainable and rapid development in the futurewent on the path of growth. In addition, the state policy is in the process of implementationbrought up in the spirit of patriotism, against the negative influence of the ideology of the third partyParticular attention is paid to the formation of a harmoniously developed generation